Tick-Borne Encephalitis Virus Vaccine-Induced Human Antibodies Mediate Negligible Enhancement of Zika Virus Infection In Vitro and in a Mouse Model - James Duehr (American Society for Microbiology, 2018)
ABSTRACT Recent reports in the scientific literature have suggested that anti-dengue virus (DENV) and anti-West Nile virus (WNV) immunity exacerbates Zika virus (ZIKV) pathogenesis in vitro and in vivo in mouse models. Large populations of immune individuals exist for a related flavivirus (tick-borne encephalitis virus [TBEV]), due to large-scale vaccination campaigns and endemic circulation throughout most of northern Europe and the southern Russian Federation. As a result, the question of whether anti-TBEV immunity can affect Zika virus pathogenesis is a pertinent one. For this study, we obtained 50 serum samples from individuals vaccinated with the TBEV vaccine FSME-IMMUN (Central European/Neudörfl strain) and evaluated their enhancement capacity in vitro using K562 human myeloid cells expressing CD32 and in vivo using a mouse model of ZIKV pathogenesis. Among the 50 TBEV vaccinee samples evaluated, 29 had detectable reactivity against ZIKV envelope (E) protein by enzyme-linked immunosorbent assay (ELISA), and 36 showed enhancement of ZIKV infection in vitro. A pool of the most highly reacting and enhanced samples resulted in no significant change in the morbidity/mortality of ZIKV disease in immunocompromised Stat2−/− mice. Our results suggest that humoral immunity against TBEV is unlikely to enhance Zika virus pathogenesis in humans. No clinical reports indicating that TBEV vaccinees experiencing enhanced ZIKV disease have been published so far, and though the epidemiological data are sparse, our findings suggest that there is little reason for concern. This study also displays a clear relationship between the phylogenetic distance between two flaviviruses and their capacity for pathogenic enhancement. IMPORTANCE The relationship between serial infections of two different serotypes of dengue virus and more severe disease courses is well-documented in the literature, driven by so-called antibody-dependent enhancement (ADE). Recently, studies have shown the possibility of ADE in cells exposed to anti-DENV human plasma and then infected with ZIKV and also in mouse models of ZIKV pathogenesis after passive transfer of anti-DENV human plasma. In this study, we evaluated the extent to which this phenomenon occurs using sera from individuals immunized against tick-borne encephalitis virus (TBEV). This is highly relevant, since large proportions of the European population are vaccinated against TBEV or otherwise seropositive.